Massive Temporalis Muscle Swelling after Decompressive Craniectomy: Case Report - Thapa, Dinesh Kumar; Nepal, Pankaj Raj; Bhattarai, Robin; Rajbanshi, Jagat Narayan; Yadav, Navin Kumar (Eastern Green Neurosurgery, 2020)
Background: Decompressive Craniectomy is a surgical procedure in neurosurgery to handle brain swelling subsequent to trauma, vascular insult, or tumor. There are different techniques and measurements of decompressive craniectomy performed worldwide. We follow the regular trauma flap involving fronto-temporo-parietal craniectomy. There have been many complications seen in these procedures, like brain herniation, malignant swelling, hydrocephalus, infection, etc. But we have encountered quite rare complications of decompressive craniectomy which had massive swelling of the temporalis muscle leading to significant mass effect and midline shift.